Assessment of the Anti-Aging Klotho Protein in Patients with COPD Undergoing Pulmonary Rehabilitation. (30th March 2017) - Pako, Judit; Barta, Imre; Balogh, Zsuzsanna; Kerti, Maria; Drozdovszky, Orsolya; Bikov, Andras; Antus, Balazs; Horvath, Ildiko; Varga, Janos
ABSTRACT: Chronic obstructive pulmonary disease (COPD) is associated with the accelerated aging of the lung. The protein klotho has been implicated in longevity, and there is some evidence that it might be involved in the pathomechanism of chronic respiratory diseases. Therefore, we aimed to examine whether the clinical condition of COPD patients is reflected in plasma klotho concentration. As plasma concentration of the protein is modulated by physiological factors that are generally improved during pulmonary rehabilitation, we hypothesized that a complex rehabilitation program may alter plasma klotho concentration. Blood samples were taken from 31 stable COPD patients. Clinical parameters such as respiratory function, 6-minute walking distance (6MWD), impact of disease (CAT), dyspnea, grip strength, chest expansion and breath holding time, smoking history, and body mass index (BMI) were evaluated. 19 patients who participated in a 3-week inpatient rehabilitation program had blood sample collection on the first, third, and last days of the program and had the above functional measurements before and after rehabilitation. Plasma klotho concentration was assessed by enzyme-linked immunosorbent assay. Klotho levels showed no correlation with clinical parameters (FEV1%, 6MWD, grip strength, CAT, smoking history, p > 0.05). Coefficient of variation of klotho measurements was 4.5% between Day 1 and Day 3. Although the rehabilitation resulted in significant improvements in 6MWD, CAT, grip strength, and chest expansion, klotho levels did not change significantly (510.1 ± 149.9 vs. 504.2 ± 139.8 pg/ml, p > 0.05). Plasma klotho concentration can be reliably measured in stable COPD; however, its levels are not correlated with clinical parameters of patients. Despite functional improvement, klotho level remains unchanged during the rehabilitation program.